2020
DOI: 10.1038/s41598-020-73489-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting rhizobacteria alleviates drought stress in potato in response to suppressive oxidative stress and antioxidant enzymes activities

Abstract: Maintenance of plant physiological functions under drought stress is normally considered a positive feature as it indicates sustained plant health and growth. This study was conducted to investigate whether plant growth-promoting rhizobacteria (PGPR) Bacillus subtilis HAS31 has potential to maintain potato growth and yield under drought stress. We analyzed trends of chlorophyll concentration, photosynthesis process, relative water content, osmolytes, antioxidants enzymes and oxidative stress, relative growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
121
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(139 citation statements)
references
References 44 publications
16
121
0
2
Order By: Relevance
“…With environmental stresses, plants produce reactive oxygen species (ROS), which at high levels can cause oxidative damage, impair membrane lipid functions, inactivate enzymes, and impede metabolic activities ( Huang et al, 2019 ). In the present study, we observed that H 2 O 2 and MDA levels were clearly higher in stressed plants, which agrees with a previous report ( Batool et al, 2020 ). PGPR application, however, obviously mitigated the high H 2 O 2 and MDA levels in stressed plants by the end of the experiment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…With environmental stresses, plants produce reactive oxygen species (ROS), which at high levels can cause oxidative damage, impair membrane lipid functions, inactivate enzymes, and impede metabolic activities ( Huang et al, 2019 ). In the present study, we observed that H 2 O 2 and MDA levels were clearly higher in stressed plants, which agrees with a previous report ( Batool et al, 2020 ). PGPR application, however, obviously mitigated the high H 2 O 2 and MDA levels in stressed plants by the end of the experiment.…”
Section: Discussionsupporting
confidence: 94%
“…PGPR application, however, obviously mitigated the high H 2 O 2 and MDA levels in stressed plants by the end of the experiment. Therefore, PGPR might suppress the production of ROS and thereby prevent oxidative-based cell membrane damage under environmental stress ( Han and Lee, 2005 ; Singh et al, 2015 ; Banik et al, 2016 ; Batool et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, rhizobacterial inoculation led to significant improvement in RWC during the vegetative stage, which is in congruence with previous reports (Naveed et al, 2014;Tiwari et al, 2016 (Batool et al, 2020). Bandeppa et al (2019) also observed significant improvement in RWC and MSI due to inoculation in mustard under drought stress condition.…”
Section: Discussionsupporting
confidence: 91%
“…The increased contents of soluble sugars under water deficit conditions ( Table 1 ) indicated that the plant used an osmoregulatory response to prevent cell dehydration as the water deficit advanced, maintaining metabolic functions and evading dehydration [ 44 , 45 , 46 ]. A similar trend has been reported in tetraploid potatoes [ 47 ], rice [ 17 ] and wheat [ 48 , 49 ]. Nevertheless, an accumulation of soluble sugar contents and low RWC values were observed under the water deficit, indicating that the accumulation of soluble sugars is not enough to maintain stable water relations ( Table 1 ).…”
Section: Discussionsupporting
confidence: 85%